2013
DOI: 10.1002/jsfa.6149
|View full text |Cite|
|
Sign up to set email alerts
|

A preliminary metagenomic study of puer tea during pile fermentation

Abstract: The dominant microbes of puer tea fermentation were bacteria in the present study, and yeasts rather than moulds accounted for the overwhelming majority of Eukaryota. The analysis of functional genes and metabolic pathways will be helpful for further study of the mechanism of puer tea fermentation at molecular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 52 publications
1
28
1
Order By: Relevance
“…Similarly, Jiang et al (2012) compared microbial communities from two different stages during the pile-fermentation of Pu-erh tea using metatranscriptomic analysis and found that Aspergillus niger was the overwhelmingly predominant species at both stages. In contrast, a preliminary metagenomic study of Pu-erh tea during pile fermentation by Lyu et al (2013) showed a significantly lower percentage of eukaryota by metagenomic analysis, indicating the dominant role of bacteria in the whole piling fermentation process. Furthermore, yeasts rather than molds accounted for the overwhelming majority of eukaryota.…”
Section: Pu-erh Teamentioning
confidence: 70%
See 3 more Smart Citations
“…Similarly, Jiang et al (2012) compared microbial communities from two different stages during the pile-fermentation of Pu-erh tea using metatranscriptomic analysis and found that Aspergillus niger was the overwhelmingly predominant species at both stages. In contrast, a preliminary metagenomic study of Pu-erh tea during pile fermentation by Lyu et al (2013) showed a significantly lower percentage of eukaryota by metagenomic analysis, indicating the dominant role of bacteria in the whole piling fermentation process. Furthermore, yeasts rather than molds accounted for the overwhelming majority of eukaryota.…”
Section: Pu-erh Teamentioning
confidence: 70%
“…Microbiota has a significant influence on the quality of Pu-erh tea, especially during the wet piling. Various kinds of bio-techniques including DGGE (Tian et al, 2013;Yang et al, 2013), pyrosequencing (Lyu et al, 2013), metatranscriptomics (Jiang et al, 2012), metagenomics and metaproteomics (Zhao et al, 2015) have been used to investigate the microbial composition during the piling process. However, the microbiological profiles of Pu-erh tea are not well understood.…”
Section: Pu-erh Teamentioning
confidence: 99%
See 2 more Smart Citations
“…Also contributing to caffeine content are growing conditions, processing techniques, and other variables. A preliminary metagenomic study of pure tea during pile fermentation (Lyu et al, 2013) revealed that major taxonomic bacterial phyla are Proteobacteria (23.56%), Actinobacteria (23.35%), and Firmicutes (11.37%), and one dominant eukaryotic phylum, Ascomycota (30.47%). Metagenomics, that is, direct analysis of the total community DNA, is able to obtain plentiful information content, including, taxonomic, metabolic potential and functional profiles of microbial communities (see Part I).…”
Section: Tea Fermentationmentioning
confidence: 99%